2015
DOI: 10.1177/1069397115609560
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cross-National Differences in Risk Through a Localized Cultural Perspective

Abstract: We examine cross-national differences in attitudes and decisions toward risk by comparing Chinese (collectivists), South Korean (collectivists, but with distinctive localized cultural norms), and Australian (individualists) undergraduate student samples from a balanced cross-cultural perspective. Individual evaluation revealed that risk was least favored by the Chinese students in their attitudes and choices, followed by the South Korean and Australian students. Unlike previous results from South Korean and Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
0
14
2
Order By: Relevance
“…Other studies have also found Chinese students were less likely than Australian students to participate in risky sexual behaviours 7,24 and more likely to delay sexual activity. 25 This may partly be explained by cultural norms surrounding sexual activity.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have also found Chinese students were less likely than Australian students to participate in risky sexual behaviours 7,24 and more likely to delay sexual activity. 25 This may partly be explained by cultural norms surrounding sexual activity.…”
Section: Discussionmentioning
confidence: 95%
“…Chinese culture is a collectivistic culture. Collectivism is the idea that an individual's life does not belong to them, but to the group or society of which they are merely a part [57]. This attitude is rooted in benevolence and conformity [58].…”
Section: Comparison Between China and Spainmentioning
confidence: 99%
“…In a collectivist culture, the relationship style emphasizes the desirability of aligning oneself with prevailing social or group norms, maintaining cohesiveness with group members, and prioritizing group decisions over individual decisions (Hofstede, 2001;Markus & Kitayama, 1991;Park, Kim & Zhang, 2016;Triandis, Bontempo, Villareal, Asai, & Lucca, 1988).…”
Section: This Regional Cultural Difference Is Associated With Northeastmentioning
confidence: 99%